(untitled) (Archaeologia Adriatica, 2025)
The high princely mounds, with large cist-type tombs made of limestone slabs and containing exceptional grave groups – as well as those with simpler grave groups consisting only ceramic sets – highlight the importance of this community and allow a more precise definition of their cultural background. These tombs are geographically confined to a small area between the Gulf of Kotor, Lake Skadar and the Zeta River plain in Montenegro. The specific funerary architecture, the crouched position of the deceased, and the remarkable metal and ceramic artefacts all point to a distinct cultural phenomenon with connections that likely extend to the Near East. These mounds with cist tombs, both those of the high elite and those with simpler ceramic offerings, represent a remarkable community that flourished during the transition from the Late Copper Age to the Early Bronze Age, between the 4th and the 3rd millennia BC. Previously, the unique stamp-rolled and excised decorations on the ceramics led to the erroneous association of these influential princes with communities in the upper Adriatic hinterland and the Ljubljansko Barje (Ljubljana Marshes), as well as with the Vučedol Culture with its origins in eastern Slavonia and Srijem on the right bank of the Danube. With due respect to the efforts of our scholarly predecessors in tracing the processes of distant prehistory, the interpretation of the ‘Montenegrin princely horizon’, which represents one of the first prehistoric elites of the highest social strata, requires precision and appropriate hierarchy. Following the discoveries of several mounds without cist tombs and royal insignia, it has become clear how large the territory of this community was, for which we propose, also with regard to the mounds in neighbouring Albanian territory, the name of the Copper/Bronze Age ‘Lake Skadar community’.